Understanding Gendered Pathways to Criminal Involvement in a Community-Based Sample: Relevance of Past Trauma with Female Offenders - Wu, Amelia S.Y. (2013)
The study explored the relevance of gender and past trauma on the pathways to criminal justice involvement in a sample of community based offenders (N = 90). The primary focus was on women and their experiences in examining the association between their traumatic past experiences and their current criminal behaviours. Results from correlation and Chi-Square analyses suggested that the presence of past trauma plays a relevant role in understanding criminal justice pathways for all offenders regardless of gender. Findings also indicated that the experience of trauma is an important factor in defining women's experiences with criminal justice in terms of the nature of offence, the types of issues they face, and the needs they present with as they manage the challenges with their mental health symptoms based on their past trauma experiences. These findings are discussed in the context of the need for gendered risk and needs assessment in addition to standard gender-neutral measures for accurate predictions of female offenders' risks and needs. Future directions should focus on understanding the link between prior trauma and women's offending behaviours